Macroalgal communities of intertidal rocky shores around Bintulu, Sarawak - Wong, Siaw Chia; Zakaria @ Ya, Muta Harah; Bujang, Japar Sidik; Arshad, Aziz; Ogawa, Hisao (Sarawak Biodiversity Centre, 2008)
Macroalgae are unique compared to seagrasses in that they are adapted to colonise range of soft to hard substrates from sand, boulders, rocks to coral reefs. Based on previous observations for examples around Similajau National Park, Bintulu macroalgae communities tend to utilize hard substrates as their striving environments. Only few species such as Caulerpa and Halimeda colonize and thrive in sandy environments. As an extension to the previous study, this present study is perform to evaluate the macroalgae community structure and their species distribution in relation to their environments, the rocky shores around Bintulu, Sarawak. Five study sites were sampled monthly during January to August 2008, in the intertidal rocky shores around Bintulu, Sarawak, Malaysia. A total of 19 families and 35 species of intertidal macroalgae were determined comprising the three divisions, Chlorophyta, Phaeophyta and Rhodophyta. Of these, Rhodophyta has the diverse representative of macroalgae with 18 species from 10 families. Chlorophyta with 12 species from seven families and Phaeopyta with five species from two families. The Family Rhodomelaceae is represented with five species namely Acanthophora spicifera, Bostrychia sp., Laurencia papillosa, Laurencia sp. and Leveillea jungermannioides. Dictyotaceae with four species, Ulvaceae and Corallinaceae with three species. Caulerpaceae, Cladophoraceae, Udoteaceae, Gelidiaceae, Gracilariaceae with two species, while the rest such as Anadyomenaceae, Polyphysaceae, Valoniaceae, Sargassaceae, Bangiaceae, Ceramiaceae, Champiaceae, Garaxauraceae, Hypneaceae and Rhodymeniaceae with one species respectively. The macroalgae community structure, the coexistence of the species in relation to their environments is described in this paper.